Bioengineering the Oxygen-Deprived Tumor Microenvironment Within a Three-Dimensional Platform for Studying Tumor-Immune Interactions - Bhattacharya, Somshuvra; Calar, Kristin; Evans, Claire; Petrasko, Mark; de la Puente, Pilar (Frontiers in Bioengineering and Biotechnology, 2020)
Oxygen deprivation within tumors is one of the most prevalent causes of resilient cancer cell survival and increased immune evasion in breast cancer (BCa). Current in vitro models do not adequately mimic physiological oxygen levels relevant to breast tissue and its tumor-immune interactions. In this study, we propose an approach to engineer a three-dimensional (3D) model (named 3D engineered oxygen, 3D-O) that supports the growth of BCa cells and generates physio- and pathophysiological oxygen levels to understand the role of oxygen availability in tumor-immune interactions. BCa cells (MDA-MB-231 and MCF-7) were embedded into plasma-derived 3D-O scaffolds that reflected physio- and pathophysiological oxygen levels relevant to the healthy and cancerous breast tissue. BCa cells grown within 3D-O scaffolds were analyzed by flow cytometry, confocal imaging, immunohistochemistry/immunofluorescence for cell proliferation, extracellular matrix protein expression, and alterations in immune evasive outcomes. Exosome secretion from 3D-O scaffolds were evaluated using the NanoSight particle analyzer. Peripheral blood mononuclear cells were incorporated on the top of 3D-O scaffolds and the difference in tumor-infiltrating capabilities as a result of different oxygen content were assessed by flow cytometry and confocal imaging. Lastly, hypoxia and Programmed death-ligand 1 (PD-L1) inhibition were validated as targets to sensitize BCa cells in order to overcome immune evasion. Low oxygen-induced adaptations within 3D-O scaffolds validated known tumor hypoxia characteristics such as reduced BCa cell proliferation, increased extracellular matrix protein expression, increased extracellular vesicle secretion and enhanced immune surface marker expression on BCa cells. We further demonstrated that low oxygen in 3D-O scaffolds significantly influence immune infiltration. CD8+ T cell infiltration was impaired under pathophysiological oxygen levels and we were also able to establish that hypoxia and PD-L1 inhibition re-sensitized BCa cells to cytotoxic CD8+ T cells. Bioengineering the oxygen-deprived BCa tumor microenvironment in our engineered 3D-O physiological and tumorous scaffolds supported known intra-tumoral hypoxia characteristics allowing the study of the role of oxygen availability in tumor-immune interactions. The 3D-O model could serve as a promising platform for the evaluation of immunological events and as a drug-screening platform tool to overcome hypoxia-driven immune evasion.